Banka teminat mektuplarına bağlı olarak verilen kontrgarantiler - Harman, Adnan (My University, 2009)
Son yıllarda yaşanan ekonomik gelişmeler, ticari ve sosyal yaşamın gelişmesi, nüfus artışı ve teknolojik gelişmelere bağlı olarak kişiler (gerçek ve tüzel kişiler) birbirleriyle daha fazla hukuki ilişkiye girmek zorunda kalmışlar. Bu şekilde ticari ilişkilerin artmasına bağlı olarak da ticari ilişkilerde eskiye oranla “güven” kurumu daha önemli hale gelmiştir. Ticari ilişkilerde güven kurumunun öneminin artmasında birer güven kurumu olan bankaların büyük etkisi olmuştur. Birer güven kurumu olan bankalar uygulamada gayrinakdi kredi işlemi adı altında yaygın olarak teminat mektubu düzenleyip genelde müşterileri olan lehtarlara vermektedirler. Bankalar, teminat mektuplarının hukuki niteliğinin garanti sözleşmesi niteliği taşıyor olmaları sebebiyle, kefalet sözleşmesinde kefilin yasadan kaynaklı sahip olduğu rücu hakkına sahip değiller. Böyle olunca riskin gerçekleşmesi ve teminat mektubunun paraya çevrilmesi neticesi muhataba ödeme yapan bankanın lehtara rücu hakkının nasıl gerçekleşeceği, dolayısıyla bankanın kendini nasıl güvenceye alacağı bu çalışma ile anlatılmaya çalışılmıştır. Bankalar kendilerini güvence altına almak için lehtar veya lehtar dışındaki üçüncü kişi gerçek veya tüzel kişilerden daha başta teminat mektubu düzenlerken kontrgaranti almaktadırlar. Lehtar veya üçüncü kişilerce bankalara verilen kontrgarantiler çok çeşitli olup; her türlü ayni veya şahsi teminat kontrgaranti olarak teminat mektubunun teminatını oluşturabilecektedir. Bu çalışma ile kontrgaranti olarak verilebilecek teminatların tamamı değil; sadece kontrgaranti amaçlı garanti sözleşmesi anlatılmaya çalışıldı.

The economical developments within the recent years, the growth of trade and social life, people (real and legal entities) have began to enter into more legal relationships depending upon the population growth and technological developments. The established “trust” became more important when compared to the rate of the old trade relations as a result of the recent growth in the new trade relationships. The banks have played a big role in the increase of the trust establishments within the trade relationships. Banks, being an entrusted establishments, under the name of contingencies have set up many letter of guarantees and give these out to its customers who are its beneficiaries. Due to the reasons that the letter of guarantees are seen as a guaranteee contract, banks do not have the authority due to the bailees legal rights to recourse within the bailing contract. As a result of this with this dissertation piece how the banks can protect itself will be explained, because in the case that a risk arises and as a result of that the letter of credit is exchanged for money the paying bank will have to explain to its beneficiaries the process of rights to recouse. In order for the banks to protect itself, banks will have to obtain a counter guarantees while setting up the letter of credit process to its beneficiaries or third parties aside from the beneficiaries who may or may not be real or legal entities. Even though these counter guarantees are of many kind that the banks receive from beneficiaries or third paries; these letter of guarantees can be used as a guarantee to the letter of guarantee in the form of either of any kind or personal counter guarantees. With this research not the whole counter guarantees that will be given in exchange for letter of guarantees; but only the counter guarantees for the purposes of an guarantee agreement will be tried to examined.
Keywords: Bankalar ve Bankacılık_Hukuk; Hukuk_Özel Hukuk